The moderating role of ethnic culture on adoption intention of generative artificial intelligence among university students - Cao, Kai; Wang, Ping; Zhao, Jie (Frontiers in Education, 2025)
This study is based on an extended model of the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) to explore the influencing factors of the adoption intention of generative artificial intelligence (GAI) in the higher-education environment of multi-ethnic regions. It also focuses on analyzing the moderating effects of ethnic culture. Data from 432 university students were collected through a questionnaire survey and analyzed using a structural equation model. The research findings are as follows: (1) The factors influencing university students' adoption intention of generative artificial intelligence include perceived ease of use, perceived usefulness, social influence, facilitating conditions, perceived learning performance, perceived learning efficiency, and user satisfaction. (2) Tool designs that are not well-adapted to ethnic cultures and the conflicts between practicality and cultural values weaken users' perceived usefulness of generative artificial intelligence, negatively moderating the impact of perceived usefulness on user satisfaction.These findings provide unique insights for university administrators in multi-ethnic regions to formulate GAI adoption policies. In addition, this study also has certain reference significance for other research in the cross-cultural field.